PERAN SELF-COMPASSION DALAM MENINGKATKAN MENTAL WELL-BEING SISWA SMA DI KOTA TASIKMALAYA - Nadia Pramesti Haningtias HANINGTIAS; Anandha Putri Rahimsyah Rahimsyah; Agung Nugraha Nugraha (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Mental well-being is an important aspect of adolescent development because it is associated with an individual's ability to function optimally, manage life challenges, and build positive social relationships. One factor that is considered to contribute to mental well-being is self-compassion. This study aims to examine the role of self-compassion in improving students' mental well-being at SMA Negeri 3 Tasikmalaya. The study employs a quantitative approach with a correlational design. The population consists of 896 students in grades X and XI, with a sample of 269 students selected through simple random sampling. Data are collected using the Self-Compassion Scale and the Warwick-Edinburgh Mental Well-Being Scale. Data analysis is conducted using descriptive statistics and simple linear regression. The findings show that most students have moderate levels of self-compassion and mental well-being. Regression analysis indicates that self-compassion plays a positive and significant role in students' mental well-being, with a contribution of 26.0 percent. These findings indicate that higher levels of self-compassion are associated with higher levels of mental well-being. Therefore, self-compassion is an important psychological factor that contributes to the enhancement of students' mental well-being and can be considered in the development of school guidance and counseling services.